METODE KREATIF DAN PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH PADA POKOK BAHASAN CARA BERPIKIR SEJARAH SISWA KELAS X MIA 1 SMA NEGERI 11 PEKANBARU - Endang Eriyani (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The purpose of this study is to increase learning outcomes of historics grade X MIA 1 Pekanbaru. This research is Classroom Action Research consisting of two cycles. The subject of this research was students of grade X SMA X NUA 1 Pekanbaru and students of SMA 11. The number of students is 36 students. The writer as a class X teacher has conducted creative and productive methods. In pre-cycle the lowest score is 69.25 and it does not require the criterion of Minimal Completness requirements which has been setted 71. The author strives to choose creative and productive methods. The learning process in the first cycle has changed in the number of class score of 2591, and the second cycle was 3021. The average score of the first cycle increased to (71.97), and the second cycle was (79.50). For calculation of completeness, students who complete pre-cycle was 41.69%; cycle I was (80.56%); cycle II was (100%). The score of cycle I was (69) and cycle II was (81) while the highest score was pre-cycle (76); cycle I was (77) and cycle II was (88). For range and criterion score, pre-cycle ranks sufficient was 15 (41.67%), low was 20 (55.56%) and very low was 1 (02.78%) while Cycle I was only 29 (80.56%) low was 7 (19.44%) and cycle II was 36 (100%). From these explanations the range and precycle criterion score were high.